Deposition and retention of meteoric 10Be in Holocene Taiwan river terraces. (1st August 2021) - Deng, Kai; Wittmann, Hella; Hsieh, Meng-Long; Yang, Shouye; von Blanckenburg, Friedhelm
Abstract: The cosmogenic meteoric 10 Be that is produced in the atmosphere and mainly scavenged by rainfall is a valuable tool for determining dates and rates of Earth surface processes. A key prerequisite for its applications is the knowledge of the long-term 10 Be depositional flux to Earth's surface. Previous efforts on obtaining 10 Be depositional fluxes include general atmospheric circulation modelling (GCM), empirical fitting of rainfall 10 Be records, and determining the inventory of soil profiles of known age. Here, we derive 10 Be depositional fluxes from Holocene river terrace 10 Be inventories across the Taiwan mountain belt. We measured 10 Be and 9 Be concentrations from three terrace profiles, with 14 C ages ranging between 3.83 and 9.05 cal. kyr BP and sampling depths of up to 6.2 m. Based on 10 Be inventories of our river terraces, the calculated long-term 10 Be depositional fluxes vary from 0.32 to 0.49 × 10 6 at/cm 2 /yr in the Taiwan orogen. We identify partial Be retention, surface erosion, multi-phase sediment deposition, and incomplete sampling depth in these terraces as potential causes of flux underestimation. When accounting for each of these factors and their uncertainties, the resulting flux estimates of each terrace show an overlapping range of 0.66–0.88 × 10 6 at/cm 2 /yr. This newly constrained flux range representative over millennial timescales is thus recommended for Earth surface applications in the fast-eroding Taiwan orogen, especially in regions with similar climatic conditions as the studied terraces. When comparing to flux estimates from other approaches, the flux from the rainfall-based fitting equation exceeds our new terrace-derived flux by more than a factor of two. We consider such high flux to be unlikely for the Taiwan orogen, and suggest that the control of precipitation on the 10 Be flux here may be overestimated in rainfall data fitting. The GCM-derived flux overestimates the 10 Be depositional flux in this setting to a smaller degree (at least 23%), which is in accordance with findings from previous global data compilation of 10 Be fluxes. Highlights: We constrained Holocene 10 Be depositional flux in Taiwan using 3 terrace profiles. Measured terrace-derived flux is 0.32–0.49 × 10 6 at/cm 2 /yr. These fluxes are similar to global flux models when considering flux uncertainties. Such local calibration is essential to use meteoric 10 Be in Earth surface studies.